Lumière en het ontstaan van de grafische groep 'De Vijf' - Minne, Joris (Brussel : Paleis der Academiën, 1964)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Masereel, Frans; Minne, Joris; Van Straten, Henri; Cantré, Jozef; Cantré, Jan-Frans.; grafische kunsten